2019
DOI: 10.1177/0033688219833131
|View full text |Cite
|
Sign up to set email alerts
|

A Move-marker List: A Study of Rhetorical Move-lexis Linguistic Realizations of Research Article Abstracts in Social and Behavioural Sciences

Abstract: While a wealth of research is available on the frequent multi-word units in academic genres, studies that exclusively link lexical sequences to the rhetorical moves in research articles (RAs) are fairly limited. This study involved compiling a corpus of 8,500 RA abstracts sampled from five disciplines of economics, law, political sciences, psychology, and sociology in social and behavioural sciences. Three to nine-word ngrams were generated using AntConc 3.4.4, which is a freeware corpus analysis toolkit. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A recent study by Khany and Malmir (2019) revealed that there are disciplinary tense variations found in the moves of RA abstracts. For example, in a past study conducted by Tankó (2017), simple present and present perfect tense were used in stating the research gap of literary RA abstracts.…”
Section: Linguistic Realization Of Ra Abstractsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Khany and Malmir (2019) revealed that there are disciplinary tense variations found in the moves of RA abstracts. For example, in a past study conducted by Tankó (2017), simple present and present perfect tense were used in stating the research gap of literary RA abstracts.…”
Section: Linguistic Realization Of Ra Abstractsmentioning
confidence: 99%
“…For example, in a past study conducted by Tankó (2017), simple present and present perfect tense were used in stating the research gap of literary RA abstracts. Meanwhile, Khany and Malmir's (2019) findings showed that simple present passive and present perfect passive were usually used in stating the gap in social sciences RA abstracts.…”
Section: Linguistic Realization Of Ra Abstractsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a past study, Khany and Malmir (2019) discovered disciplinary tense variations in the moves of RA abstracts. Tankó (2017), for example, revealed that simple present and present perfect tense are usually employed in presenting the research gap of literary RA abstracts in a previous study.…”
Section: Linguistic Realization Of Ra Abstractsmentioning
confidence: 99%
“…The past three decades have witnessed a growing interest in the study of research articles (RAs) from different perspectives. The bulk of the studies has focused on rhetorical move structure (Kanoksilapatham, 2015;Khany & Malmir, 2019;Wannaruk & Amnuai, 2016), lexico-grammatical features (Green, 2019;Staples, & Reppen, 2016;Zhang, 2019), and disciplinary variation (Crossley et al, 2017;Jiang, 2017).…”
Section: Introductionmentioning
confidence: 99%